The Asteraceae (Compositae) from Laraos district (Yauyos, Lima, Peru) - Beltrán, Hamilton (2016)
For the district Laraos 155 species of asteraceae grouped into 66 genus, 12 tribes and 3 subfamilies are recorded. Senecio, Baccharis and Werneria are genus more wealth. Senecio larahuinensis and Conyza coronopifolia are new records for the flora of Peru as the first new species; further 35 species are new reports for Lima. Dichotomous keys for the identification of tribes, genus and species present.